Epidemiology, diagnosis and management of patients with biliary dyskinesia and sphincter of Oddi dysfunction: a survey of Indian gastroenterologists - Mandot, Ameet; Patil , Sandeep; Gupta, Shivesh (International Journal of Research in Medical Sciences, 2023)
Background: A cross-sectional, physician-based survey was conducted to address the relative lack of data on the awareness about and management of biliary dyskinesia and sphincter of Oddi dysfunction among Indian gastroenterologists. Methods: A structured questionnaire containing questions on epidemiology, etiology, clinical presentation, diagnostic investigations, prognosis and management was used. Physician responses were analyzed as descriptive statistics and reported as frequency and percentages. Results: A total 146 gastroenterologists across 137 cities participated in the survey. Majority (76.0%) of physicians stated that <10% of their patients with cholecystitis get diagnosed with BD, while 84.7% stated that <25% of patients with BD have SOD. SOD and BD were reported to be common in females <50 years. Patients recovering from major surgeries/stroke/heart attack/sepsis/extensive trauma were identified by 53.0% of physicians to be at risk for BD. Majority of physicians (69.4%) reported that irritable bowel syndrome (IBS) was a major risk factor for SOD. Cholescintigraphy and hepatobiliary scintigraphy were investigations of choice for BD and SOD according to 55.5% and 33.6% of physicians, respectively. Sepsis was identified as a frequent complication of BD (45.2%). Laparoscopic cholecystectomy was identified by 64.4% participants to result in partial resolution of symptoms in many patients. Calcium channel blockers and antispasmodics were preferred by 55.9% and 30.8% physicians for functional gall bladder disorder, respectively. IBS was the most common indication for prescribing the antispasmodic pinaverium, with the primary objective of pain relief. Conclusions: Findings from this survey provide insights for further research on BD and SOD in India.